Impact of Natural Honey on Betta sp. strain Plakat Candy Masculinization - agustina bahriul bangsil; Juliana; G. Ahmad (Airlangga University, 2023)
Betta sp. is an ornamental fish that is favoured by all ornamental fish hobbyists in Indonesia. Various strains of this fish have been produced by many farmers. However, almost all of the most popular strains are male. This study aims to determine the effect of different lengths of natural honey soaking on the masculinisation of hickey fish. The method used in this study was a completely randomised design with 4 treatments and 3 replicates. The treatment used in this study is the length of immersion (22 - 26 hours) of each treatment compared to the control (without immersion) which was then maintained for 60 days. The results of this study showed that immersion using natural honey on larvae in a 5 ml/L honey solution had no significant effect on masculinisation of hippopotamus. However, the best masculinisation was found with 22 hours of immersion at 63.6% and the lowest without immersion at 49.6%.